Coexistence or aggression? Insight into the influence of phosphate on Cr(VI) adsorption onto aluminum-substituted ferrihydrite. (December 2018) - Zhu, Lijun; Fu, Fenglian; Tang, Bing
Abstract: This work aims to explore how phosphate affected hexavalent chromium (Cr(VI)) removal and the interaction between the aluminum-substituted ferrihydrite (shortened as Fh-Al) and Cr(VI) in the presence of phosphate. The adsorption behaviors of Cr(VI) on Fh-Al were tested in a synthetic solution containing Cr(VI) and phosphate. Series of characterization techniques, such as X-ray diffraction analysis, transmission electron microscopy equipped with the energy dispersive X-ray spectroscopy, attenuated total reflection Fourier transform infrared spectroscopy, and X-ray photoelectron spectroscopy, have been used to analyze the Fh-Al before and after the adsorption of Cr(VI) in the presence of phosphate. Desirable adsorption performances of Cr(VI) occurred at pH value 3.0. Cr(VI) showed low affinity to Fh-Al due to the negative influence of phosphate. Addition of phosphate forced Cr(VI) out of Fh-Al surfaces like an "invader". The adsorption process was better described by the Langmuir isotherm model, and the adsorption capacity of Cr(VI) in the presence of 9.3 mg/L phosphate was 42.09 mg/g. The mechanism for Cr(VI) removal by Fh-Al under the influence of phosphate was developed as follows: (1) electrostatic interaction, (2) the formation of FeOCr complexes, and (3) the formation of ternary complexes between Fh-Al and Cr(VI) using phosphate as medium. Graphical abstract: Highlights: Factors influencing Cr(VI) and phosphate removal by Fh-Al were studied. Phosphate had strong inhibitory influence on Cr(VI) adsorption. Three ways of Cr(VI) adsorption on Fh-Al were found in the presence of phosphate.